Cloud point extraction coupled with back extraction: a green methodology in analytical chemistry - Shivpoojan Kori (Oxford University Press, 2021)
Recently, cloud point extraction (CPE) coupled with back extraction (BE) has been suggested as a promising alternative to liquid-liquid extraction. In CPE, non-ionic surfactants in aqueous solutions form micelles and the solution becomes turbid when heated to the cloud point temperature. Microwave- or ultrasonic-assisted BE can be performed after CPE and before injection of the sample for instrumental analysis by ultraviolet-visible spectroscopy, high-performance liquid chromatography, gas chromatography, gas chromatography-mass spectrometry, or liquid chromatography-mass spectrometry. This article reviews selected published scientific research on the application of CPE-BE to the determination of alkaloids, drugs and organophosphorus compounds from several complex matrices. This method could be scaled-up for use in forensic science.